CURRENT STATE AND PERSPECTIVES OF EDUCATIONAL WORK OF THE MINORS CONDEMNED IN THE INSTITUTIONS OF THE FSIN OF RUSSIA - Nesterov Artyom Y. (Scientific Journal of Pedagogy and Economics, 2020)
The article presents the current state of educational work with juvenile convicts in educational colonies of the Federal Penitentiary Service of Russia. The author determines that the recidivism of youth and adolescents in the current period remains one of the acute problems in the Russian Federation. So, juvenile delinquency is a powerful source of self-determination of crime as such. Today, juvenile delinquency produces crime of young people (from 14 to 17 years old), translates negative criminal experiences into the future, which, according to the laws of social education, again “returns” to tomorrow's teenagers as the “social heritage” of previous generations. And also do not forget that juvenile delinquents are the social base of organized and recidivism in modern Russia. It can also be noted that by committing repeated criminal offenses the offender is firmly convinced of his impunity. Relapse of crimes committed by juveniles sentenced to suspended sentences (or corrective labor), or to insignificant real terms of imprisonment, emphasizes the ineffectiveness of the sentence, which is reflected in the increase in the number of repeated criminal offenses committed by minors. Therefore, it is very real that, due to the weakness and inefficiency of penitentiary resocialization in prisons, the number of crimes committed by convicts, but in a more perverse form, may increase in a few years (not excluded in the composition of an organized criminal group). And also juvenile delinquency promotes the spread of a criminal way of thinking and a way of behavior in a “healthy” teenage environment, leading to its criminal infection. So, Taoist wisdom says - ... be afraid of your thoughts, for they are the beginning of your actions - Lao Tzu (VI – V centuries BC). Teenage crime causes harm to the personal development of the juvenile offender himself, thereby contributing to the continuation of the criminal activity of the minor. Based on the foregoing, juvenile delinquency should be considered as one of the most serious and significant socio-legal problems of modern Russian society. In the article, the author proposes a “model” of the development of penitentiary institutions, includes a description of the goals and objectives of the Educational Center of the Federal Penitentiary Service of Russia, its functional and organizational structure, conditions for serving sentences and detention of juvenile convicts. The model of the educational center of the Federal Penitentiary Service of Russia for juvenile convicts is presented.